Richhpal Singh Meena v. Ghasi: Past Eclipse of India’s Substantive Criminal Law in Contemporary Operation - Lalli, Jaideep Singh (Kathmandu School of Law Review, 2021)
The Indian Supreme Court’s verdict in Richhpal Singh Meena v. Ghasi is a marked peripeteia in the legal position on the applicability of offences under the two sub-chapters of Chapter XVI of the IPC in the heads of sections dealing with ‘Offences Affecting Life’ and ‘Hurt’. In essence, this ruling declared that scenarios that end with death of the victim will mandatorily have to be only covered by the sub-chapter ‘Offences Affecting Life’, making ‘actus reus of fatal results’ the determinant for choosing the offence for which the accused is to be convicted. After providing a factual frame of reference, this paper recapitulates the key elements of the Court’s reasoning in arriving at this principle. The main thrust of the paper lies in its analysis of the Court’s faulty neologisms and legally inconsistent alterations in the yardsticks that govern which cases fall under either of the two heads. This paper argues that the Court’s ratio decidendi and the principles it has evolved represent nothing short of insouciance towards decades of clarificatory precedent and that they are ex facie since Richhpal’s ruling engenders injustice in situations where the intention is to only cause hurt, but death results regardless of the intention transpired. As a judgment made in 2014, this ruling continues to breed iniquitous convictions even to this day. It is this examination of the judgment’s myopia for the past and its eclipse on the present delivery of justice that represents the central thesis of this paper.